2015
DOI: 10.1111/jjns.12080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐fidelity patient simulation led clinical reasoning course: Focused on nursing core competencies, problem solving, and academic self‐efficacy

Abstract: There is a need for the development of effective instructional methods to improve learning outcomes in nursing education. Future research is needed related to simulation education as well as management strategies so that learning outcomes can be achieved within different students' learning style.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
1
24
1
Order By: Relevance
“…Two of the studies were descriptive, cross-sectional studies that identified the breakdown of Kolb learning preferences in their cohorts. 25,26 One of the three studies that attempted to correlate Kolb learning preferences with a learning outcome found no association between dental students' learning style preference and either GPA or the senior students' choice of specialty practice. 9 The other two studies attempting to find a correlation were conducted by Shinnick and Woo and Tsingos and colleagues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the studies were descriptive, cross-sectional studies that identified the breakdown of Kolb learning preferences in their cohorts. 25,26 One of the three studies that attempted to correlate Kolb learning preferences with a learning outcome found no association between dental students' learning style preference and either GPA or the senior students' choice of specialty practice. 9 The other two studies attempting to find a correlation were conducted by Shinnick and Woo and Tsingos and colleagues.…”
Section: Resultsmentioning
confidence: 99%
“…Assimilators, divergers, and balanced learning style all increased knowledge after high fidelity simulation 25 No correlation between learning style preference and dental school GPA 9 Reflective observation (assimilators and divergers) performed better in a social pharmacy course 28…”
Section: Kolb Learning Style Inventory Correlation Between Learning Smentioning
confidence: 98%
“…Four stations were included in this OSCE based upon clinical experts' experience at our institution. The overall reliability in the present study was 0.791, which is a desirable level of reliability for high-stakes tests, such as certi cation [30][31][32]. The number of stations in this OSCE was, thus, appropriate to assess the competence of the NNPs in our study.…”
Section: Discussionmentioning
confidence: 69%
“…Four stations were included in this OSCE based upon clinical experts’ experience at our institution. The overall reliability in the present study was 0.791, which is a desirable level of reliability for high-stakes tests, such as certification [ 30 32 ]. The number of stations in this OSCE was, thus, appropriate to assess the competence of the NNPs in our study.…”
Section: Discussionmentioning
confidence: 93%